Comparing rat and rabbit embryo-fetal developmental toxicity data for 379 pharmaceuticals: on systemic dose and developmental effects. (28th May 2017) - Theunissen, Peter T.; Beken, Sonia; Beyer, Bruce; Breslin, William J.; Cappon, Gregg D.; Chen, Connie L.; Chmielewski, Gary; de Schaepdrijver, Luc; Enright, Brian; Foreman, Jennifer E.; Harrouk, Wafa; Hew, Kok-Wah; et al.
Abstract: A database of embryo-fetal developmental toxicity (EFDT) studies of 379 pharmaceutical compounds in rat and rabbit was analyzed for species differences based on toxicokinetic parameters of area under the curve (AUC) and maximum concentration ( C max ) at the developmental lowest adverse effect level (dLOAEL). For the vast majority of cases (83% based on AUC of n = 283), dLOAELs in rats and rabbits were within the same order of magnitude (less than 10-fold different) when compared based on available data on AUC and C max exposures. For 13.5% of the compounds the rabbit was more sensitive and for 3.5% of compounds the rat was more sensitive when compared based on AUC exposures. For 12% of the compounds the rabbit was more sensitive and for 1.3% of compounds the rat was more sensitive based on C max exposures. When evaluated based on human equivalent dose (HED) conversion using standard factors, the rat and rabbit were equally sensitive. The relative extent of embryo-fetal toxicity in the presence of maternal toxicity was not different between species. Overall effect severity incidences were distributed similarly in rat and rabbit studies. Individual rat and rabbit strains did not show a different general distribution of systemic exposure LOAELs as compared to all strains combined for each species. There were no apparent species differences in the occurrence of embryo-fetal variations. Based on power of detection and given differences in the nature of developmental effects between rat and rabbit study outcomes for individual compounds, EFDT studies in two species have added value over single studies.